Three growth factors induce proliferation and differentiation of neural precursor cells in vitro and support cell-transplantation after spinal cord injury in vivo - Younsi, Alexander; Zheng, Guoli; Scherer, Moritz; Riemann, Lennart; Zhang, Hao; Tail, Mohamed; Hatami, Maryam; Skutella, Thomas; Unterberg, Andreas; Zweckberger, Klaus (Stem cells international, 2020)
Stem cell therapy with neural precursor cells (NPCs) has the potential to improve neuroregeneration after spinal cord injury (SCI). Unfortunately, survival and differentiation of transplanted NPCs in the injured spinal cord remains low. Growth factors have been successfully used to improve NPC transplantation in animal models, but their extensive application is associated with a relevant financial burden and might hinder translation of findings into the clinical practice. In our current study, we assessed the potential of a reduced number of growth factors in different combinations and concentrations to increase proliferation and differentiation of NPCs invitro. After identifying a "cocktail" (EGF, bFGF, and PDGF-AA) that directed cell fate towards the oligodendroglial and neuronal lineage while reducing astrocytic differentiation, we translated our findings into anin vivomodel of cervical clip contusion/compression SCI at the C6 level in immunosuppressed Wistar rats, combining NPC transplantation and intrathecal administration of the growth factors 10 days after injury. Eight weeks after SCI, we could observe surviving NPCs in the injured animals that had mostly differentiated into oligodendrocytes and oligodendrocytic precursors. Moreover, "Stride length" and "Average Speed" in the CatWalk gait analysis were significantly improved 8 weeks after SCI, representing beneficial effects on the functional recovery with NPC transplantation and the administration of the three growth factors. Nevertheless, no effects on the BBB scores could be observed over the course of the experiment and regeneration of descending tracts as well as posttraumatic myelination remained unchanged. However, reactive astrogliosis, as well as posttraumatic inflammation and apoptosis was significantly reduced after NPC transplantation and GF administration. Our data suggest that NPC transplantation is feasible with the use of only EGF, bFGF, and PDGF-AA as supporting growth factors.